(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
This research contributes to the need to improve oral expression skills in English in students of the different specialties at the University of Granma. It suggests a system of practical activities to contribute to the development of this skill at an A2 level, as suggested by the Common European Framework of Reference for Languages ​​(CEFR), and taking into account the difficulties detected in the students of this Center of higher studies , which limit the achievement of this level. The activities are important because they were developed from the characteristics of this type of student and developed by the authors of this work themselves, so they do not appear in any specialized bibliography. As a result of its application, positive changes have been observed in students related to better linguistic performance, allowing their certification to level A2. In general, this work can be used as a practical tool in other English courses at other Cuban universities.